Implementasi Projek Penguatan Profil Pelajar Pancasila (P5): Kearifan Lokal Di SMP Negeri 4 Kubung Kabupaten Solok - Wila Agustika Rahayu; Merika Setiawati; Ikhwan Ikhwan (Student Scientific Creativity Journal, 2023)
This study aims to analyze the implementation of the Pancasila Student Profile Strengthening Project (P5) with the theme of Local Wisdom. This type of research is qualitative with a phenomenological approach and naturalistic methods. The results showed that the implementation of P5 at SMP Negeri 4 Kubung consisted of several stages: first, designing P5 with details; form the P5 team through meetings, identify the readiness of the education unit, dimensions of P5, theme of P5 namely Local Wisdom, time allocation, and develop modules modified from existing modules, as well as a strategy for reporting the results of P5. Second, managing the project from starting P5 with introduction and contextualization, optimizing implementation with P5 action, and closing the project with celebration. Third, process the assessment by summarizing formative and summative assessments. Reporting with a P5 report card once a year in the even semester. Fourth, evaluation through reflection and meetings as well as follow-up in the form of continuing batik activities on the theme of local wisdom.